Physical and physiological changes of Crambe abyssinica Hochst seed during maturation - Silva, Ana Paula de Oliveira (2020)
Determination of seed-maturation indicators enables the identification of the ideal moment for harvest to achieve the best production and conservation potential. Our objective here was to evaluate some physical and physiological changes of crambe (Crambe abyssinica Hochst) seeds as possible indicators of seed maturation. Crambe flowering was monitored in Dourados, Mato Grosso do Sul, Brazil. Plants were tagged, and 13, 22, 26, and 28 days after the initiation of flowering, the seeds were collected and following physical attributes evaluated: length, diameter, total mass, dry matter and water content. Physiological quality of the seeds was assessed using the germination test, by registering the percentage of normal seedlings and dormant seeds, immediately after each harvest, and again after six months of storage. The water-absorption curves were characterized as a function the seed-development stages. All physical attributes were observed to increase because of the accumulation of reserve substances during seed development, except for water content, which gradually decreased from 72.2% at the start of development to 29.5% at maturity. At 28 days after anthesis the germination percentage of crambe seeds at physiological maturity was only 17%, indicating that they became dormant while maturing. However, seed germination rate was 89% after six months of storage, indicating that dormancy was almost fully overcome after this period.